Growth Your Mindset to Increase Resilience in College Students - Miranti Rasyid; Aulia Suhesty; Diah Rahayu; Nur Najiba Indayani; Ayusha Adhikarapandita (Indonesian Journal Of Educational Research and Review, 2023)
Academic stress and psychological pressure is most often felt by students. One of the factor great factor is person's resilience ability that greatly influenced by the mindset of the person in seeing their experiences and life. This study aims to analyze the effectiveness of the influence of growth your mindset training to increase student resilience. The research design used was a pretest-posttest control group design. The research subjects were 30 students who were divided into 15 students in the experimental group and 15 students in the control group. Student resilience was measured using a student resilience scale. Data analysis used Wilcoxon and Mann-Whitney U Test using SPSS 25 Software for Windows. The results of the analysis using the Wilcoxson test which compared the resilience scores of students in the experimental group between before and after training showed a value of Z = -2.901, p = 0.004 (p <0.05) meaning that there were differences in resilience scores among students before and after being given the growth your mindset training treatment, so that there is a significant increase in resilience after being given the growth your mindset training treatment. The results of the analysis using the Mann-Whitney U Test showed a value of Z = -3.744, p = 0.000 (p <0.05) meaning that there were differences in the level of resilience in students between the experimental group that was given the growth your mindset training treatment and the control group that was not given the growth your mindset training treatment.